2021
DOI: 10.1187/cbe.21-02-0024
|View full text |Cite
|
Sign up to set email alerts
|

A New Measure of Students’ Perceived Conflict between Evolution and Religion (PCoRE) Is a Stronger Predictor of Evolution Acceptance than Understanding or Religiosity

Abstract: College biology students’ perceived conflict with their religions was found to be the strongest predictor of evolution acceptance compared with student religiosity, religious affiliation, and understanding of evolution. A new instrument to measure perceived conflict between religion and evolution (PCoRE) is provided for researchers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 74 publications
1
26
0
2
Order By: Relevance
“…These findings indicate that community college students may benefit more than university students from having discussions about how evolution and religion do not necessarily have to be in conflict. We did not have enough community college students in this study who took our perceived conflict scale to include it as a variable in our models predicting acceptance ( n = 123), but perceived conflict has been shown to be the biggest factor influencing college students’ evolution acceptance ( Barnes et al. , 2021b ), and given that community college students perceive a higher conflict with their religions and evolution compared with university students, community college students may benefit from explicit discussion and reflection about the potential compatibility of religion and evolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings indicate that community college students may benefit more than university students from having discussions about how evolution and religion do not necessarily have to be in conflict. We did not have enough community college students in this study who took our perceived conflict scale to include it as a variable in our models predicting acceptance ( n = 123), but perceived conflict has been shown to be the biggest factor influencing college students’ evolution acceptance ( Barnes et al. , 2021b ), and given that community college students perceive a higher conflict with their religions and evolution compared with university students, community college students may benefit from explicit discussion and reflection about the potential compatibility of religion and evolution.…”
Section: Discussionmentioning
confidence: 99%
“…We measured perceived conflict using a recently published survey of students’ perceived conflict between their religions and evolution ( Barnes et al. , 2021b ).…”
Section: Methodsmentioning
confidence: 99%
“…Religious beliefs are among the factors most investigated as predictors to the low acceptance of evolution in several studies, especially among some age groups, religious affiliations, and nationalities, mainly Christian American students [ 10 , 20 , 21 ]. Barnes et al [ 22 ] conducted a study with 1898 students in eight states of the United States and found that 56.5% of students perceived that evolution is atheistic, with a higher percentage of Catholic and other Christian students.…”
Section: Introductionmentioning
confidence: 99%
“…Evolution is an important concept of biology ( 1 , 2 ), yet many introductory biology students do not fully accept evolution ( 3 ). Students’ rejection of evolution often stems from their perceived conflict between evolution and their religious identity, which is the strongest factor predicting students’ evolution acceptance ( 4 6 ). The specific religious affiliation of a student may influence the level of perceived conflict that they feel between their religion and evolution.…”
Section: Introductionmentioning
confidence: 99%